HSP90-incorporating chaperome networks as biosensor for disease-related pathways in patient-specific midbrain dopamine neurons. Issue 1 (December 2018) - Kishinevsky, Sarah; Wang, Tai; Rodina, Anna; Chung, Sun; Xu, Chao; Philip, John; Taldone, Tony; Joshi, Suhasini; Alpaugh, Mary; Bolaender, Alexander; Gutbier, Simon; Sandhu, Davinder; et al.
Abstract Environmental and genetic risk factors contribute to Parkinson's Disease (PD) pathogenesis and the associated midbrain dopamine (mDA) neuron loss. Here, we identify early PD pathogenic events by developing methodology that utilizes recent innovations in human pluripotent stem cells (hPSC) and chemical sensors of HSP90-incorporating chaperome networks. We show that events triggered by PD-related genetic or toxic stimuli alter the neuronal proteome, thereby altering the stress-specific chaperome networks, which produce changes detected by chemical sensors. Through this method we identify STAT3 and NF-κB signaling activation as examples of genetic stress, and phospho-tyrosine hydroxylase (TH) activation as an example of toxic stress-induced pathways in PD neurons. Importantly, pharmacological inhibition of the stress chaperome network reversed abnormal phospho-STAT3 signaling and phospho-TH-related dopamine levels and rescued PD neuron viability. The use of chemical sensors of chaperome networks on hPSC-derived lineages may present a general strategy to identify molecular events associated with neurodegenerative diseases. The early molecular events that ultimately lead to neuronal cell death in pathologies such as Parkinson's disease are poorly understood. Here the authors use pluripotent stem-cell-derived human midbrain neurons and chemical biology tools to gain molecular level insight into the events induced by toxic and genetic stresses that mimic those occurring during neurodegeneration.